All-Arthroscopic Segond Fracture Fixation in Association With Anterior Cruciate Ligament Repair - Matteo Romano Cantagalli, M.D.; Alessandro Carrozzo, M.D.; Giulia Rescigno, M.D.; Natale Criseo, M.D.; Matt Daggett, D.O.; Bertrand Sonnery-Cottet, M.D., Ph.D.; Edoardo Monaco, M.D. (Arthroscopy Techniques)
Anterior cruciate ligament (ACL) reconstruction techniques for ACL injury are still the gold standard, but today primary repair has been an effective alternative in the appropriate patient population. The goal of ACL surgery is to restore the rotational stability and to control the pivot shift phenomenon. For this reason, the treatment of the associated lesions such as anterolateral ligament and capsule, Segond fracture (SF), and lateral meniscus posterior root are recommended. This Technical Note shows the pearls and pitfalls of an all-arthroscopic technique of SF fixation with ACL repair combined with external meniscus suture and SF fixation.